Pelatihan Membaca Al-Qur’an dengan Metode Iqro’ untuk Para Ibu Lanjut Usia (Lansia) - Luluk Indarti; Lukluk Nur Mufidah (Pusat Riset dan Inovasi Nasional, 2025)
Training to read the Qur'an with Iqro ' method for elderly women is one of the efforts of community empowerment in the field of religion. This activity was held at the Nurul Huda mosque, Wanengpaten Village, Gampengrejo District, Kediri, on September 11-30, 2024. Iqro ' method was chosen because it has been widely known by the elderly and proven effective in improving the ability to read the Qur'an gradually. This training aims to train the ability to read the Qur'an, especially in terms of correct pronunciation hijaiyah letters (Makhorijul letters). The implementation of the activities involves an age-friendly approach, with the use of simple modules and intensive mentoring. The results of this training showed a significant improvement in the ability of participants in reading the Qur'an, especially in the mastery of Tajweed and clarity of pronunciation of letters. This Program is expected to be a model that can be replicated in various other areas in order to improve Qur'anic literacy among elderly women. In addition to providing technical training, this program also plays a role in building participants ' confidence to be active in religious activities in their environment. The learning process is designed in stages, starting from the introduction of hijaiyah letters, the correct pronunciation according to makhraj, to the application of Tajweed rules in reading the verses of the Qur'an. Assistance is carried out intensively by paying attention to the physical condition and memory of the elderly, so that the learning atmosphere becomes more conducive and enjoyable. The evaluation results showed that most of the participants experienced significant progress, both in reading fluency, pronunciation accuracy, and basic understanding of Tajweed law. Another positive impact is the establishment of closer social relationships between participants, so this training also contributes to strengthening the social bonds of the community. The success of this program indicates that the iqro learning model combined with an age-friendly approach can be an effective strategy to improve Qur'anic literacy among the elderly, while strengthening religious values in the community